2020
DOI: 10.1002/aelm.202000062
|View full text |Cite
|
Sign up to set email alerts
|

Few‐Layer Organic Crystalline van der Waals Heterojunctions for Ultrafast UV Phototransistors

Abstract: Organic UV photodetectors using a transistor architecture can yield higher photoresponsivity than diode‐based devices because of the presence of a gate electrode. However, a long‐term issue of these phototransistor devices is the slow response speed, which hinders their practical applications. Here, organic UV phototransistors are constructed using few‐layer organic crystalline van der Waals (vdW) heterojunctions as the photoactive layers. The thickness of the photoactive layers is even less than the exciton d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Thus, this indicates the formation of C 8 ‐BTBT/F 16 CuPc heterojunctions. [ 27 ] We further characterized the morphologic properties of the heterojunctions via atomic force microscopy (AFM) (Figure 1d,e and Figure S1d (Supporting Information)). The results showed that the thicknesses of the C 8 ‐BTBT, PMMA, and F 16 CuPc films are ≈5.7, 6.0, and 10.2 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this indicates the formation of C 8 ‐BTBT/F 16 CuPc heterojunctions. [ 27 ] We further characterized the morphologic properties of the heterojunctions via atomic force microscopy (AFM) (Figure 1d,e and Figure S1d (Supporting Information)). The results showed that the thicknesses of the C 8 ‐BTBT, PMMA, and F 16 CuPc films are ≈5.7, 6.0, and 10.2 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…2D OSs with well-defined interfaces and precisely adjusted thicknesses have various of potential for physical implementation of phototransistors because their tunable energy gap can cover a large spectrum range from near-infrared to ultraviolet [53,54,[130][131][132][133]. Low photogating efficiency, low carrier mobility, and short photo-induced exciton diffusion distance in bulk organic materials, on the other hand, impede the development of highly efficient and fast response phototransistors [134][135][136][137]. In order to ensure photo-generated exciton separation, the thickness of the photoactive layer should be lowered below 10 nm [138].…”
Section: Circuit-type Synapsementioning
confidence: 99%
“…Furthermore, the interlayer screening effect found in thick photoactive materials impedes photocurrent decay characteristics. Guo et al built a few-lay N,N -(1-hexyl)-1,4,5,8-naphthalenetetracarboxydiamide (NDI-C 6 )/C 8 -BTBT van der Waals heterojunction to overcome the exciton-diffusion bottleneck and restrict exciton separation/recombination in the year 2020 [134] (Inset of figure 10(a)). As presented in figure 10(a), the authors extracted the photoresponsivity and sensitivity to evaluate the device's performance, which are 1.78 A/W and 50, respectively.…”
Section: Circuit-type Synapsementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] To date, 2DOCS-based field-effect transistors (FETs) have experienced impressive mobility enhancement; [17][18][19] the charge-carrier-transport and injection physics have also been explicitly elucidated. [20][21][22] These fascinating breakthroughs have thus greatly motivated performance optimization of tremendous organic functional devices, including transistor memories, [23,24] photodetectors, [25,26] light-emitting diodes, [27] and biosensors. [28,29] To further expand the practical application of available 2DOCSs to cost-effective, high-throughput manufacturing functional devices and integrated circuits, patterning of 2DOCSs, which has never been experimentally demonstrated, is undoubtedly an essential prerequisite.…”
Section: Patterning 2d Organic Crystalline Semiconductors Via Thermalmentioning
confidence: 99%